Analysis of interface states of metal-insulator-semiconductor photodiode with n-type silicon by conductance technique - Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2008)
A metal-insulator-semiconductor photodiode (MIS-PD) as active layer with n-type silicon as interdigitated Schottky electrodes has been fabricated. The current-voltage characteristics, density of interface States and photovoltaic properties of the MIS-PD diode have been investigated. The diode has a metal-insulator-semiconductor configuration with ideality factor higher than unity. The electronic parameters (ideality factor, series resistance and barrier height) of the diode were found to be 1.94, 2.23 x 10(4) Omega and 0.74, respectively. At voltages between 0.13 and 0.50 V, the charge transport mechanism of the diode is controlled by space charge-limited current mechanism. The interface state density of the diode was found to vary from 5.54 x 10(12) to 5.67 x 10(12) eV(-1) cm(-2) with bias voltage. The Au/SiO2/n-Si/Al device shows a photovoltaic behavior with a maximum open circuit voltage V., of 97.7 mV and short-circuit current I-sc of 17.4 mu A under lower illumination intensities. The obtained electronic parameters confirm that the Au/SiO2/n-Si/Al diode is a MIS type photodiode. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: metal-insulator-semiconductor; interfacial state density; photodiode